Conducting a fully mobile and randomised clinical trial for depression: access, engagement and expense. Issue 1 (4th February 2016) - Anguera, Joaquin A; Jordan, Joshua T; Castaneda, Diego; Gazzaley, Adam; Areán, Patricia A
Abstract : Importance: Advances in mobile technology have resulted in federal and industry-level initiatives to facilitate large-scale clinical research using smart devices. Although the benefits of technology to expand data collection are obvious, assumptions about the reach of mobile research methods ( access ), participant willingness to engage in mobile research protocols ( engagement ), and the cost of this research ( cost ) remain untested. Objective: To assess the feasibility of a fully mobile randomised controlled trial using assessments and treatments delivered entirely through mobile devices to depressed individuals. Design: Using a web-based research portal, adult participants with depression who also owned a smart device were screened, consented and randomised to 1 of 3 mental health apps for treatment. Assessments of self-reported mood and cognitive function were conducted at baseline, 4, 8 and 12 weeks. Physical and social activity was monitored daily using passively collected phone use data. All treatment and assessment tools were housed on each participant's smart phone or tablet. Interventions: A cognitive training application, an application based on problem-solving therapy, and a mobile-sensing application promoting daily activities. Results: Access : We screened 2923 people and enrolled 1098 participants in 5 months. The sample characteristics were comparable to the 2013 US census data. Recruitment via Craigslist.org yielded the largest sample. Engagement : Study engagement was high during the first 2 weeks of treatment, falling to 44% adherence by the 4th week. Cost : The total amount spent on for this project, including staff costs and β testing, was 314 264 over 2 years. Conclusions and relevance: These findings suggest that mobile randomised control trials can recruit large numbers of participants in a short period of time and with minimal cost, but study engagement remains challenging. Trial registration number: NCT00540865.